Land Use and Land Cover (LULC) classes in Ogbaru Local Government Area of Anambra State, Nigeria - Christian, Iguocha Arinze (Peneliti.net, 2025)
Land Use and Land Cover (LULC) classification plays a critical role in understanding the dynamics of environmental change and its impact on land resources. The evolution of these land cover types is essential for assessing the region's land management strategies, agricultural productivity, and environmental conservation. This study investigates the Land Use and Land Cover (LULC) classes in Ogbaru Local Government Area (LGA) of Anambra State, Nigeria, using satellite imagery to analyze spatial and temporal changes from 1986 to 2020. This study explores Land Use and Land Cover (LULC) classes in Ogbaru Local Government Area (LGA) using both primary and secondary data sources. The area, with a population of 261,018 as of 2010, is characterized by tropical climate, agriculture, and fishing. Primary data were collected through GPS-based field surveys for ground-truthing, while secondary data were derived from LANDSAT imagery (1980, 2000, 2020) with 30-meter spatial resolution. Image pre-processing was conducted, and supervised classification using the Maximum Likelihood Classification (MLC) method was applied for LULC classification. Pearson’s correlation analysis was utilized to explore the relationship between LULC and land surface temperature. Five distinct LULC classes were identified: Forested Areas, Urban Surfaces, Bare Surfaces, Light Vegetation, and Water Bodies. The study utilized LANDSAT satellite data to assess the dynamics of these classes over a 34-year period. Results show a significant shift in land cover, with urban areas increasing from 1% of the total land area in 1986 to 5% in 2020, reflecting the impact of urbanization and infrastructural development. Conversely, forested areas decreased substantially, while light vegetation initially increased but later declined. Water bodies experienced minor changes, while bare surfaces showed a gradual rise, especially between 1986 and 2002. These findings highlight the rapid urbanization and the corresponding decline in natural vegetation, underscoring the need for sustainable land management strategies to balance development with environmental preservation in Ogbaru. The study demonstrates the utility of satellite imagery in monitoring LULC changes for effective urban planning and resource management.